Effect of a Multimodal Analgesic Protocol on Short-Term and Long-Term Opioid Use After Orthopaedic Trauma. Issue 8 (6th August 2022) - Oyler, Douglas R.; Slade, Emily; Slavova, Svetla; Matuszewski, Paul E.; Lei, Feitong; Herndon, Brooke; Johnson, Shannon; Moghadamian, Eric S.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To determine whether the use of a multimodal analgesic protocol reduced short-term and long-term opioid use in patients hospitalized after orthopaedic trauma. Design: Retrospective pre–post intervention study. Setting: Regional, academic, Level 1 trauma center in Central Kentucky. Patients/Participants: Patients were hospitalized after orthopaedic injury before (n = 393) and after (n = 378) the implementation of a multimodal analgesic protocol. Intervention: The intervention involved a multimodal analgesic protocol consisting of acetaminophen, ibuprofen/ketorolac, gabapentinoids, skeletal muscle relaxants, and standardized doses of opioids plus standardized pain management education before hospital discharge. Main Outcome Measurements: End points included discharge opioid prescription, days' supply and daily morphine milligram equivalent (MME), and long-term opioid use after hospitalization. Opioid use in the 90 days before and after hospitalization was assessed using state prescription drug monitoring program data. Results: Discharge opioid prescription rates were similar in the intervention and control cohorts [79.9% vs. 78.4%, odds ratio (OR) 1.30 (0.83–2.03), P = 0.256]. Patients in the intervention cohort received a shorter days' supply [5.7 ± 4.1 days vs. 8.1 ± 6.2 days, rate ratio 0.70 (0.65–0.76), P < 0.001] and lower average daily MME [34.8 ± 24.9 MME vs. 51.5 ± 44.0 MME, rate ratio 0.68 (0.62–0.75), P < 0.001]. The incidence of long-term opioid use was also significantly lower in the intervention cohort [7.7% vs. 12.0%, OR 0.53 (0.28–0.98), P = 0.044]. Conclusions: Implementation of a multimodal analgesic protocol was associated with reductions in both short-term and long-term opioid use, including long-term opioid therapy, after orthopaedic trauma. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.